EFEK DARI ECO-LABEL, GREEN PROMOTION DAN BRAND IMAGE TERHADAP PURCHASE DECISION PADA SUSU GREENFIELDS - Ulul Azmi; Mikrad (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
Nowadays, the aspect of people's decision in buying a product sees its impact on the environment. PT Greenfields in its marketing implements an environmentally friendly packaging system and carries out CSR that is oriented towards environmental empowerment. This study is oriented to examine eco-label, green promotion, and brand image in purchase decisions on Greenfields Milk purchase in Neroktog, Tangerang. This groundwork method is quantitative with a sample of 100 people calculated applying the Lemeshow formula because the population is unknown. The researcher distributed questionnaires to Greenfields Milk consumers, thus finding that the eco-label variable affects purchase decisions. The hypothesis is accepted and the eco-label variable shows a positive and significant effect. Then the green promotion variable does not effect the purchase decision. Then the brand image variable affects purchase decisions. Thus the hypothesis is accepted and this variable shows a positive and significant impact. Simultaneously, the three independent variables influence the dependent variable based on the results of the F test calculation.This finding supports the importance of environmentally friendly attributes for packaged milk products because it can improve consumers in deciding to purchase products